The Scholar as Human : Research and Teaching for Public Impact - Bartel, Anna Sims, 1973-; Castillo, Debra A. (Book collections on Project MUSE., 2020)
"This book collects diverse perspectives from scholars in literature and the arts, theater and performance, anthropology, sociology, and law about the value of the humanities. It grew out of Cornell's Mellon Diversity Seminar in 2016-17 where fifteen public humanists met for a series of self-directed weekly seminars in which they could be open about their fears and desires, challenges, and hopes. The essays provide a practical and intellectual model for how humanists deepen their scholarship through rigorous engagement with their own humanity"--